2020
DOI: 10.1177/1460458220950853
|View full text |Cite
|
Sign up to set email alerts
|

Mobile applications for breast cancer survivorship and self-management: A systematic review

Abstract: The use of mobile technology and mobile apps has become pervasive in our daily lives for completing a variety of daily tasks. Mobile health (mHealth) apps can provide an accessible platform for self-management among breast cancer (BC) survivors, as they recover from not just the intensive cancer treatments, but also their associated side-effects. They also offer a means to learn about survivorship topics and connect with peer survivors online, irrespective of their geographical location. This study is an attem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 47 publications
0
35
0
Order By: Relevance
“…Such campaigns hopefully can increase women’s BCS uptake because a prior study has shown that mobile health (mHealth) apps can improve screening behavior and self-management, especially among BC survivors. 57 - 59 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such campaigns hopefully can increase women’s BCS uptake because a prior study has shown that mobile health (mHealth) apps can improve screening behavior and self-management, especially among BC survivors. 57 - 59 …”
Section: Discussionmentioning
confidence: 99%
“…Such campaigns hopefully can increase women's BCS uptake because a prior study has shown that mobile health (mHealth) apps can improve screening behavior and self-management, especially among BC survivors. [57][58][59] Similarly, healthcare workers should educate women about the importance of annual routine BCS. Effective communication using verbal persuasion and social influence by healthcare workers recommended by Bandura 54 can boost women's ability and decisions to receive CBE or mammogram.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst the most important benefits identified by the patients are easy access to personalized information, convenience, better information on their health, and the ability to communicate more easily with healthcare professionals [ 5 , 6 ]. So far, most studies have focused on patients with cancer [ 7 , 8 , 9 ], patients with cardiovascular diseases [ 10 , 11 ], or older adults with [ 12 ] or without cognitive impairment [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Smartphone technology represents an opportunity to deliver practical solutions for people affected by cancer at a scale that was previously unimaginable, such as information, appointment monitoring, and improved access to cancer support services [1]. Mobile health (mHealth) apps can provide an accessible platform for self-management among breast cancer survivors, as they recover from not just the intensive cancer treatments, but also their associated side-effects [2]. Breast cancer is a discrediting disease and its treatment can bring genuine results that have a physical and mental effect.…”
Section: Introductionmentioning
confidence: 99%